Radiolabeling of Fibrinogen Using the Iodogen Technique - Knight, Linda C; Budzynski, Andrei Z; Olexa, Stephanie A (Thrombosis and Haemostasis, 1981)
The properties of human fibrinogen labeled with 125-Iodine using Iodogen (1, 3, 4, 6-tetrachloro-3α, 6α-diphenylglycoluril) as an oxidizing agent were compared with those of an iodine monochloride labeled counterpart. It was found that thrombin clottability, binding to staphylococci, the relative specific radioactivity of the Aα, Bβ, and γ chains and in vivo clearance from plasma in rabbits were the same in these two labeled fibrinogen preparations. Labeling efficiency was higher when iodogen was used. It is concluded that human fibrinogen labeled with radioiodine using the Iodogen technique is suitable for studies in vitro and in vivo.
Keywords: Fibrinogen; Radioiodination techniques; Iodogen; Radiolabeled proteins